Electrooxidation-induced reverse switching in azobenzene-based photoswitches - Hussain, Zarah; Schatz, Dominic; Oberhof, Nils; Franz, Evanie; Schauermann, Daniel; Dreuw, Andreas; Wegner, Hermann A.; Brummel, Olaf; Libuda, Jörg (The journal of physical chemistry. C, Energy, materials, and catalysis, 2025)
Photoswitches, which reversibly switch between isomeric forms upon light exposure, offer promising applications in optical computing, photoresponsive materials, and molecular energy storage. Efficient and controllable back-isomerization is essential for practical applications and can be achieved electrochemically. In this study, we explore how electrochemical oxidation governs the back-conversion of the azobenzene-based photoswitch 4,4′-(diazene-1,2-diyl)bis(N,N′-diethylaniline) (A-AZO). Combining in situ photoelectrochemical infrared reflection absorption spectroscopy with density functional theory calculations, we show that A-AZO undergoes reversible two-step oxidation, forming singly and doubly oxidized species (A-AZO1+ and A-AZO2+), with the positive charge primarily localized on the nitrogen atoms of the amino groups. Photochemically, (E)-A-AZO isomerizes to its (Z)-form. Upon electrochemical triggering, the oxidized (Z)-A-AZOx+ species act as catalytic intermediates that accelerate the back-conversion to the (E)-isomer. This autocatalytic reaction proceeds with high selectivity and requires minimal external energy input, making it particularly attractive for energy-efficient switching in molecular systems.